PENGARUH KARAKTERISTIK INDIVIDU DAN INSENTIF KEHADIRAN TERHADAP MOTIVASI, KEPUASAN KERJA DAN KINERJA TENAGA KEPENDIDIKAN IPB UNIVERSITY - Lolita Anggarini; M. Syamsul Maarif; Siti Amanah (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
This study aims to analyze the effect of individual characteristics and attendance incentives on motivation, job satisfaction and performance of education staff at IPB University. Data collection was obtained through distributing questionnaires to 305 education staff from 1,282 populations using disproportionate random sampling through grouping in work units. Data analysis was performed using the Chi-Square cross tabulation test and Structural Equational Modeling-Partial Least Square (SEM-PLS). Chi-Square test results indicated that educational characteristics have a significant relationship with motivation, job satisfaction and performance, while job characteristics have a significant relationship with job satisfaction and performance of education staff. SEM-PLS analysis resulted in the conclusion that individual characteristics have a stronger influence on motivation than job satisfaction, but it has no attachment to performance. Besides, attendance incentives have a greater influence on motivation than performance. The influence of motivation is more dominant on job satisfaction than on performance. Job satisfaction has a positive and significant effect on performance. It is expected that high level of job satisfaction can also result in good performance. Keywords: attendance, job satisfaction, motivation, performance, SEM-PLS